Log in to add a comment

Log in to add a comment

(1) substitution

(2) elimination

(3) cross multiplication

here i am solving this by substitution

so , 2x+y=1

from here , y=1-2x ------------(1)

putting (1) in 3x - 4y =18

so, 3x - 4(1-2x) = 18

3x - 4 +8x = 18

11x - 4 = 18

11x = 22

dividing by 11

x = 2 -------------(2)

putting (2) in (1)

y=1-2(2)

y=-3

3x-4y=18(2 equation)

since in 2nd equation has 4y multiply the first equation with 4, u get

(8x+4y=4)+(3x-4y=18) u get

8x+4y=4

3x-4y=18

+4y and -4y get cancelled we get 11x=22 so x = 2

substitute x=2 in (1st or second equation)

so we get

2(2)+y=1

4+y=1

y=1-4

y= -3

so x=2 and y= -3

pick my answer as the best plz!!!!!!!!!!!